2018
DOI: 10.1111/bcp.13576
|View full text |Cite
|
Sign up to set email alerts
|

Does patient reporting lead to earlier detection of drug safety signals? A retrospective comparison of time to reporting between patients and healthcare professionals in a global database

Abstract: AimsTo explore if there is a difference between patients and healthcare professionals (HCPs) in time to reporting drug–adverse drug reaction (ADR) associations that led to drug safety signals.MethodsThis was a retrospective comparison of time to reporting selected drug–ADR associations which led to drug safety signals between patients and HCPs. ADR reports were selected from the World Health Organization Global database of individual case safety reports, VigiBase. Reports were selected based on drug–ADR associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 22 publications
4
14
0
Order By: Relevance
“…We identified a high proportion (36%) of ADEs not listed in the corresponding summary of product characteristics, which, given the only recent availability of the monitored drugs, are largely based on randomized clinical trial data. This finding appears consistent with the results of other studies which showed that consumer reports have the potential to identify new ADEs that were not previously included in the summary of product characteristics, and that the ADEs are sometimes reported earlier by consumers than by healthcare professionals [28][29][30]. Nevertheless, surprising differences among the monitored glucoselowering drugs were found in the present study, with the highest proportions of unlabelled ADEs being reported by new users of DPP-4 inhibitors alone.…”
Section: Discussionsupporting
confidence: 92%
“…We identified a high proportion (36%) of ADEs not listed in the corresponding summary of product characteristics, which, given the only recent availability of the monitored drugs, are largely based on randomized clinical trial data. This finding appears consistent with the results of other studies which showed that consumer reports have the potential to identify new ADEs that were not previously included in the summary of product characteristics, and that the ADEs are sometimes reported earlier by consumers than by healthcare professionals [28][29][30]. Nevertheless, surprising differences among the monitored glucoselowering drugs were found in the present study, with the highest proportions of unlabelled ADEs being reported by new users of DPP-4 inhibitors alone.…”
Section: Discussionsupporting
confidence: 92%
“…For example, it has been found that patients often provide detailed clinical stories that describe their experiences and the impact of ADRs on their quality of life [40,42]. Recent studies using VigiBase data also show that patient reports can contribute to identifying possible safety issues [40,43]. From the reports in VigiBase it is notable that the proportion of female reports is slightly larger for patients compared to other groups of reporters.…”
Section: Discussionmentioning
confidence: 99%
“…Improving the access of spontaneous notifications to patients is an important goal for all regulatory agencies. By increasing the number of reports implementing pharmacovigilance databases, they theoretically allow to detect relevant signals of adverse‐reactions to drugs . We have previously shown that spontaneous notifications from patients could be reliably taken in consideration apart from their degree of severity .…”
Section: Discussionmentioning
confidence: 99%